Algebra Questions

Question Number 11074 by Joel576 last updated on 10/Mar/17

$$\frac{\mathrm{2}}{\left({x}\:−\:\mathrm{1}\right)^{\mathrm{2}\:} }\:+\:\frac{\mathrm{4}}{\left({y}\:+\:\mathrm{2}\right)^{\mathrm{2}} }\:+\:\frac{\mathrm{5}}{{z}^{\mathrm{2}} }\:=\:\frac{\mathrm{9}}{\mathrm{4}} \\$$$$\frac{\mathrm{4}}{\left({x}\:−\:\mathrm{1}\right)^{\mathrm{2}} }\:−\:\frac{\mathrm{2}}{\left({x}\:+\:\mathrm{2}\right)^{\mathrm{2}} }\:−\:\frac{\mathrm{1}}{{z}^{\mathrm{2}} }\:=\:\frac{\mathrm{1}}{\mathrm{2}} \\$$$$\frac{\mathrm{3}}{\left({z}\:−\:\mathrm{1}\right)^{\mathrm{2}} }\:+\:\frac{\mathrm{6}}{\left({y}\:+\:\mathrm{2}\right)^{\mathrm{2}} }\:−\:\frac{\mathrm{2}}{{z}^{\mathrm{2}} }\:=\:\mathrm{1} \\$$$$\\$$$$\left({z}\:−\:\mathrm{1}\right)^{\mathrm{2}} \:+\:\left({y}\:+\:\mathrm{2}\right)^{\mathrm{2}} \:\:+\:{z}^{\mathrm{2}} \:=\:??? \\$$

Answered by ridwan balatif last updated on 10/Mar/17

$$\mathrm{is}\:\mathrm{it}\:\frac{\mathrm{3}}{\left(\mathrm{x}−\mathrm{1}\right)^{\mathrm{2}} }+\frac{\mathrm{6}}{\left(\mathrm{y}+\mathrm{2}\right)^{\mathrm{2}} }−\frac{\mathrm{2}}{\mathrm{z}^{\mathrm{2}} }=\mathrm{1}? \\$$

Commented by Joel576 last updated on 11/Mar/17

Commented by Joel576 last updated on 11/Mar/17

$$\mathrm{tapi}\:\mathrm{bisa}\:\mathrm{juga}\:\mathrm{soalnya}\:\mathrm{typo} \\$$

Commented by ridwan balatif last updated on 11/Mar/17

$$\mathrm{let}:\frac{\mathrm{1}}{\left(\mathrm{x}−\mathrm{1}\right)^{\mathrm{2}} }=\mathrm{a},\:\:\frac{\mathrm{1}}{\left(\mathrm{y}+\mathrm{2}\right)^{\mathrm{2}} }=\mathrm{b},\:\frac{\mathrm{1}}{\mathrm{z}^{\mathrm{2}} }=\mathrm{c} \\$$$$\mathrm{2a}+\mathrm{4b}+\mathrm{5c}=\frac{\mathrm{9}}{\mathrm{4}}...\left(\mathrm{1}\right) \\$$$$\mathrm{4a}−\mathrm{2b}−\mathrm{c}=\frac{\mathrm{1}}{\mathrm{2}}...\left(\mathrm{2}\right)\rightarrow\mathrm{8a}−\mathrm{4b}−\mathrm{2c}=\mathrm{1} \\$$$$\mathrm{3a}+\mathrm{6b}−\mathrm{2c}=\mathrm{1}...\left(\mathrm{3}\right) \\$$$$\mathrm{elimination}\:\mathrm{variable}\:\mathrm{c}\:\mathrm{in}\:\mathrm{equation}\:\left(\mathrm{2}\right)\mathrm{and}\:\left(\mathrm{3}\right) \\$$$$\mathrm{8a}−\mathrm{4b}−\mathrm{2c}=\mathrm{1} \\$$$$\mathrm{3a}+\mathrm{6b}−\mathrm{2c}=\mathrm{1} \\$$$$−−−−−−−−\:\left(−\right) \\$$$$\mathrm{5a}−\mathrm{10b}=\mathrm{0} \\$$$$\mathrm{a}=\mathrm{2b} \\$$$$\mathrm{elimination}\:\mathrm{variable}\:\mathrm{c}\:\mathrm{in}\:\mathrm{equation}\:\left(\mathrm{1}\right)\:\mathrm{and}\:\left(\mathrm{2}\right) \\$$$$\mathrm{2a}+\mathrm{4b}+\mathrm{5c}=\frac{\mathrm{9}}{\mathrm{4}} \\$$$$\mathrm{20a}−\mathrm{10b}−\mathrm{5c}=\frac{\mathrm{5}}{\mathrm{2}} \\$$$$−−−−−−−−−−\left(+\right) \\$$$$\mathrm{22a}−\mathrm{6b}=\frac{\mathrm{19}}{\mathrm{4}} \\$$$$\mathrm{22a}−\mathrm{3}\left(\mathrm{2b}\right)=\frac{\mathrm{19}}{\mathrm{4}} \\$$$$\mathrm{19a}=\frac{\mathrm{19}}{\mathrm{4}} \\$$$$\mathrm{a}=\frac{\mathrm{1}}{\mathrm{4}} \\$$$$\mathrm{a}=\mathrm{2b}\rightarrow\mathrm{b}=\frac{\mathrm{1}}{\mathrm{8}} \\$$$$\mathrm{2}\left(\frac{\mathrm{1}}{\mathrm{4}}\right)+\mathrm{4}\left(\frac{\mathrm{1}}{\mathrm{8}}\right)+\mathrm{5c}=\frac{\mathrm{9}}{\mathrm{4}} \\$$$$\frac{\mathrm{1}}{\mathrm{2}}+\frac{\mathrm{1}}{\mathrm{2}}+\mathrm{5c}=\frac{\mathrm{9}}{\mathrm{4}} \\$$$$\mathrm{5c}=\frac{\mathrm{5}}{\mathrm{4}} \\$$$$\mathrm{c}=\frac{\mathrm{1}}{\mathrm{4}} \\$$$$\mathrm{so},\:\mathrm{a}=\frac{\mathrm{1}}{\mathrm{4}}\rightarrow\left(\mathrm{x}−\mathrm{1}\right)^{\mathrm{2}} =\mathrm{4} \\$$$$\:\:\:\:\:\:\:\mathrm{b}=\frac{\mathrm{1}}{\mathrm{8}}\rightarrow\left(\mathrm{y}+\mathrm{2}\right)^{\mathrm{2}} =\mathrm{8} \\$$$$\:\:\:\:\:\:\mathrm{c}=\frac{\mathrm{1}}{\mathrm{4}}\rightarrow\mathrm{z}^{\mathrm{2}} =\mathrm{4} \\$$$$\therefore\left(\mathrm{x}−\mathrm{1}\right)^{\mathrm{2}} +\left(\mathrm{y}+\mathrm{2}\right)^{\mathrm{2}} +\mathrm{z}^{\mathrm{2}} =\mathrm{4}+\mathrm{8}+\mathrm{4}=\mathrm{16} \\$$$$\mathrm{ANSWER}:\:\mathrm{E} \\$$